Persepsi Manfaat, Persepsi Kemudahan, Norma Subjektif, Kualitas Informasi dan Minat Penggunaan: Studi pada Pengguna E-commerce - Aditya, I Made Fery; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p18, 2021)
E-commerce is a general concept in the process of buying and selling products or services through the internet network. The Technology Acceptance Model theory explains the factors that influence the behavior of users of information systems, The purpose of this study is to obtain empirical evidence of the effect of perceived usefulness, perceived ease of use, subjective norms, and quality of information on interest in using e-commerce. This research was conducted on all active college students majoring in Accounting class 2016 at the Faculty of Economics and Business, Udayana University, totaling 115 college students. The sampling method used in this study was saturated sampling and the data analysis technique in this study used multiple linear regression analysis. Based on the analysis conducted, it was found that perceived usefulness, perceived ease of use, subjective norms and quality of information had a positive effect on the interest in using e-commerce. Keywords: Perceived Usefulness; Perceived Ease Of Use; Subjective Norms; Information Quality; E-Commerce.